Conflict and cooperation in local water governance: Inventory of local water-related events in tiraque District, Bolivia - Vladimir Cossio; Rocío Bustamante; Thomas Skielboe (Danish Institute for International Studies (DIIS), 2010)
Recent years have witnessed an increasing focus on water as a source of conflict. So far, much of the focus has been on the risk for transboundary water conflicts. Our current knowledge on local water conflicts is however more limited, and trends to be based on sporadic accounts of local water conflicts rather than on systematic empirical evidence. At the same time, the extent and nature of local water cooperation is often overlooked, just as we know little about the particular role of the poorest in water conflict and cooperation. the lack of such knowledge jeopardizes current initiatives taken in many developing countries to ensure a more efficient and equitable water governance. To fill this gap, the Competing for Water research programme developed a conceptual and methodological framework for developing comprehensive inventories of local water-related conflict and cooperation. This report documents the results of applying this framework in Tiraque district, Cochabamba, Bolivia, and discusses the implications.
Keywords: 330; Wasserversorgung; Wasserpolitik; Wasserwirtschaft; Konflikt; Kooperation; Cochabamba (Dep.); Bolivien